Percutaneous nephrostomy in cervical cancer patients: a retrospective analysis - Deborah Pinagé Alves de Lima; Carolina do Nascimento Matias Teixeira; Marilia de Brito Abath; Fernando Antonio Nunes Raposo; Silvia Borges Fontan (Brazilian Journal of Oncology)
OBJECTIVES: To evaluate the outcome of patients with cervical carcinoma submitted to percutaneous nephrostomy due to malignant ureteral obstruction. MATERIAL AND METHODS: Retrospective cohort study with data obtained from medical records of patients diagnosed with cervical carcinoma with renal dysfunction (AKIN = stage 2) undergoing PCN for malignant obstructive uropathy between January 2019 and December 2020 at a tertiary hospital in Recife, Brazil. RESULTS: We evaluated 31 patients submitted to percutaneous nephrostomy. Median age was 50 years, and the majority of women were non-white with an elementary education. Twenty-one patients required hemodialysis before the procedure, and 61.9% of them recovered renal function after nephrostomy. Bleeding and nephrostomytube displacement were the leading causes of complications in the first 30 days (69%). Median overall survival after the procedure was 8.7 months. Survival was significantly worse in patients with anemia, ECOG performance status = 2 (p=0.04), pre-nephrostomy dialysis (p=0.01), and not recovery of renal function after PCN. CONCLUSIONS: Performing urinary diversion through percutaneous nephrostomy seems to offer greater benefits in patients with better functionality. Given the morbidity and complications inherent to percutaneous nephrostomy, the profile of patients who benefit most from the procedureremains unclear. Referrals for the procedure must be individualized and consider the patient's desire, treatment perspectives, and functionality.